Constructing semiconductive crystalline microporous materials by Coulomb interactions. Issue 35 (23rd August 2017) - Wang, Guan-E; Yao, Ming-Shui; Cai, Min-Lan; Xiu, Jing-Wei; Li, Yan-Zhou; Xu, Gang; Guo, Guo-Cong
Abstract : A new strategy has been demonstrated to construct conducting microporous crystalline materials, where inorganic components and organic molecules pack with each other through long distance Coulomb interactions. The two compounds show typical semiconductive properties, relatively high thermal stability, interesting selective adsorption and electrical response to methanol and ethanol. Abstract : Crystalline materials possessing both porous and conductive properties would create a great opportunity for novel electrical applications in fuel cells, batteries and sensors. However, these kinds of materials are rarely reported. Here, we report a new type of conducting porous crystalline material constructed by long distance Coulomb interactions among inorganic and organic components. The compound in this work shows a microporous structure, typical semiconductive properties, selective adsorption and an interesting electrical response to methanol and ethanol.